2020
DOI: 10.3389/fvets.2020.570414
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Probiotics to Increase the Immune Power of Colostrum in Dogs

Abstract: Wide differences in Ig concentration in canine colostrum have been reported. Thus, some litters can be at risk of passive immune transfer failure. Present study evaluated if supplementation with MOS, FOS, E. faecium and L. acidophilus along pregnancy increases colostrum quality. Twenty Great Dane bitches were divided into 4 groups. Control group (CG) received standard diet, only. Diet was supplemented with pre-and probiotics in other 3 study groups during: the last (1WG), last 2 (2WG), and last 4 (4WG) weeks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Few animal studies have investigated how pre- and/or probiotics fed to epitheliochorial pregnant mammals interact with the immune composition of mammary secretions. In dogs, pregnant bitches fed a mixture of fructo-oligosaccharides, mannan-oligosaccharides, E. faecium and L. acidophilus expressed significantly more IgG, IgM and IgA in colostrum ( 57 ). Possible mechanisms are the modulation of immunoglobulin secretion by the maternal microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Few animal studies have investigated how pre- and/or probiotics fed to epitheliochorial pregnant mammals interact with the immune composition of mammary secretions. In dogs, pregnant bitches fed a mixture of fructo-oligosaccharides, mannan-oligosaccharides, E. faecium and L. acidophilus expressed significantly more IgG, IgM and IgA in colostrum ( 57 ). Possible mechanisms are the modulation of immunoglobulin secretion by the maternal microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Another trial shows that prebiotics benefit IgE and IgA secretion and enhance intestinal barrier function [ 69 , 70 ]. Interestingly, in addition to increasing intestinal immunoglobulins, probiotics can promote the IgG, IgM, and IgA levels in the colostrum, thereby improving neonatal clinical conditions and immune function [ 71 ].…”
Section: The Function Of Probiotics and Prebiotics On Canine Intestin...mentioning
confidence: 99%
“…Prebiotics and probiotics could interact with the immune composition of mammary secretions, influencing the distribution and relative abundance of specific immune responses in dogs and cats [ 129 ]; inducing higher luminal secretions of IgA in the small intestine; enhancing the immunoglobulins concentration in mammary secretions, by means of the immune entero-mammary link in monogastric species. As a consequence, higher levels of immunoglobulins could be transferred to puppies [ 130 ]. It was demonstrated that pre- and probiotics administration to the mother during pregnancy increases colostrum quality (higher immunoglobulin concentrations).…”
Section: Nutraceutical Compounds In Newbornsmentioning
confidence: 99%